SISTEM INFORMASI MONITORING PERSEDIAAN SEPEDA MOTOR DENGAN METODE RATA-RATA BERBASIS WEB PADA PT NUSANTARA SAKTI SALATIGA - Muhartin Muhartin (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2019)
PT. Nusantara Sakti Salatiga or often referred to as NSS is an automotive company or dealer of two-wheeled motor vehicles with the Honda brand, which is located at JL. Cutting No. 100 Salatiga. This company has a very rapid development, this is evidenced in 2017 the stock inventory increased by 25%. Motorcycle inventory monitoring information system with a web-based average method at PT. Nusantara is an accounting information system created to overcome data processing problems which are still in the form of manual bookkeeping so that the data is less valid and less effective time to present reports and even data storage has not been recorded which results in easy data loss. Existing problems can be overcome by creating an accounting information system Monitoring Inventory and making a data storage information system that is valid and effective. Designing a good computerized system that is expected to assist officers in presenting reports quickly and accurately. Data collection methods used are the questionnaire method and Likert scale. The method of designing a motorcycle inventory monitoring information system is made using the methodology of R&D, Flowchat, DFD, ERD and Normalization. The program used to create this application uses the PHP and MySQL programming languages ​​as Database management. The results of this study indicate that the motorcycle inventory monitoring information system with a web-based average method at PT. The archipelago can be used to solve inventory processing problems that include data collection of data, supplier data collection, data entry of goods, data collection of goods out, and inventory using the average method can make reports that are valid, effective and efficient so that reports can be accounted for and risk error will be minimal.